Improving potato cultivation using siphons for partial root-zone drying irrigation: a case study in the Blue Nile river basin, Ethiopia - Yactayo, W.; Ramírez, D.; German, T.; Worku, A.; Abeb, A.; Harahagazwe, D.; Mares, V.; Mendiburu, F. de; Quiróz, R. (Walter de Gruyter GmbH, 2017)
Partial root-zone drying (PRD) is an irrigation technique which consists of alternating the water supply from one furrow to another, and keeping the other one dry during the weekly alternation period. Studies assessing PRD in potato have reported a 30-50% of water savings with no tuber yield reductions and an increase of antioxidant concentrations and marketable tubers. In this study, we adapted the PRD technique to rural Ethiopian conditions and compared it against the customary (C) irrigation practiced by local farmers. Two PRD alternatives were evaluated; with (PRDs) and without (PRDw) locally made flexible-hose siphons. Only PRDs showed no significant differences in total (35.8±1.6 t ha-1) and marketable (34.2±1.6 t ha-1) tuber yield when compared with customary irrigation (39.4±1.3 and 37.6±1.2 t ha-1 corresponding to total and marketable yield, respectively). The PRDw was more water restricted, showing significantly lower total (29.7±1.1 t ha-1) and marketable (27.6±1.2 t ha-1) yields. PRDs had the benefit of a better control of applied water allowing a saving of 50% of the irrigation water without negatively affecting yield. The use of the siphons PRD technique provides options for saving scarce water and reaching out to many smallholder farmers who are in serious need of irrigation water in the Blue Nile river basin.